Identification of key genes and metabolites involved in meat quality performance in Qinchuan cattle by WGCNA - Hengwei Yu; Zhimei Yang; Jianfang Wang; Huaxuan Li; Xuefeng Li; Entang Liang; Chugang Mei; Linsen Zan (Journal of Integrative Agriculture, 2024)
Understanding the genetic and metabolic elements that impact meat quality is crucial to improving production and meeting consumer demands in the beef sector. Differences in meat quality among various muscle areas in beef cattle can impact pricing in the market. Despite progress in genomics, the specific genes and metabolites that affect meat quality characteristics in Qinchuan cattle remain inadequately understood. Therefore, this study aims to evaluate the meat quality characteristics of four specific muscle locations (tenderloin, striploin, high rib, and ribeye muscles) in Qinchuan bulls, including 10 traits (total protein content (TPC), intramuscular fat (IMF), non-esterified fatty acid (NEFA), meat color (L*, a*, and b*), shear force (SF), cooking loss (CL), pH0, and pH24). This experiment uses transcriptome, metabolome sequencing, and sophisticated analytical methodologies such as weighted gene co-expression network analysis (WGCNA) and protein–protein interaction networks (PPI) to identify the key genes and metabolites associated with specific traits. The findings highlight three notable genes (NDUFAB1, NDUFA12, and NDUFB7) linked to intramuscular fat (IMF), three key genes (CSRP3, ACAA3, and ACADVL) correlated with non-esterified fatty acids (NEFA), and one crucial gene (CREBBP) influencing meat color. In conclusion, this investigation offers a new perspective on the differences in bovine muscle locations and contributes to the molecular understanding of bovine meat quality. Future research endeavors could delve deeper into the identified genes and pathways to enhance beef cattle's quality and yield.